2021
DOI: 10.1139/apnm-2020-0923
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid ameliorates neonatal isolation-induced autistic like behaviors in rats: epigenetic modifications of BDNF and GFAP promotors

Abstract: The current study investigated the role of epigenetic dysregulation of brain derived neurotrophic factor (BDNF) and glial fibrillary acidic protein (GFAP) genes and oxidative stress as possible mechanisms of autistic-like behaviors in neonatal isolation model in rats and the impact of folic acid administration on these parameters. Forty Wistar albino pups were used as follows: control, folic acid administered, isolated, and isolated folic acid treated groups. Isolated pups were separated from their mothers for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Daily folic acid supplementation of this neonatal isolation rat model reversed the changes seen in offspring. This suggests the potential use of folic acid, a potent methyl-donor and neuroprotectant, as a viable intervention method to alleviate autistic and anxiety-like behaviors in offspring [56].…”
Section: Folatementioning
confidence: 99%
See 1 more Smart Citation
“…Daily folic acid supplementation of this neonatal isolation rat model reversed the changes seen in offspring. This suggests the potential use of folic acid, a potent methyl-donor and neuroprotectant, as a viable intervention method to alleviate autistic and anxiety-like behaviors in offspring [56].…”
Section: Folatementioning
confidence: 99%
“…Decrease in NSC proliferation and differentiation and increase in neuronal apoptosis in fetal mouse brain [52] Supplementation of high folate diet to Wistar rat offspring Decrease in Pomc methylation and improved glucose response of offspring to glucose load [55] Folate Supplementation in neonatal isolation rat model Hypomethylation of BDNF and increase in its expression + mitigated autistic and anxiety-like behavior in offspring [56] Supplementation with high methyl-vitamins gestational diet (B12, B6, folate) in Wistar rats Hypermethylation of hypothalamic Pomc and 5-Htr2a + leptin and insulin resistance in offspring [36] High maternal folate and low VitB12 in pregnant women…”
Section: Folatementioning
confidence: 99%
“…Epigenetic dysregulation of astrocytes and reduced astrocyte cell proportions have been linked to psychiatric disorders associated with ELS, including major depressive disorder [ 136 ]. One study found that maternal separation led to reduced promoter CpG methylation of glial fibrillary acidic protein (Gfap) , an intermediate filament protein expressed only in astrocytes [ 137 ], in the frontal cortex of adolescent male rats [ 138 ]. There is also some evidence of ELS-induced epigenetic reprogramming of oligodendrocytes, the myelinating cells of the CNS that enable saltatory nerve conduction and axon integrity.…”
Section: Epigenetics and Cellular Programmingmentioning
confidence: 99%
“…Accordingly, maternal/paternal folate status due to both genetically inherited predispositions and/or folate intake might differentially affect the global embryonic DNA methylation program [51,155]. Of note, in a preclinical model of autism it has been recently demonstrated that epigenetic dysregulation (i.e., hypomethylation) of key genes (brain-derived neurotrophic factor gene BDNF and glial fibrillary acidic protein GFAP gene) involved in the induced autistic-like behaviors in a neonatal isolation model, can be reversed by folic acid administration [156]. Interestingly, the treatment effects were mediated by the epigenetic regulation of BDNF and GFAP by restoring the hypomethylated status of the two gene promoters and by antioxidant effects, opening stimulating translational applications.…”
Section: The Role Of Epigenetics and Genetics: The Paradigm Of The Fo...mentioning
confidence: 99%